Development of the Genealogical FamilySearch Database and Expanding Its Use to Map and Measure Multiple Generations of American Migration - Samuel M. Otterstrom; Brian E. Bunker; Michael A. Farnsworth (Genealogy, 2021)
Genealogical research is full of opportunities for connecting generations. Millions of people pursue that purpose as they put together family trees that span hundreds of years. These data are valuable in linking people to the people of their past and in developing personal identities, and they can also be used in other ways. The purposes of this paper are to first give a short history of the development and practice of family history and genealogical research in the Church of Jesus Christ of Latter-day Saints, which has developed the FamilySearch website, and second, to show how genealogical data can illustrate forward generation migration flows across the United States by analyzing resulting patterns and statistics. For example, descendants of people born in several large cities exhibited distinct geographies of migration away from the cities of their forebears.